2019
DOI: 10.1016/j.chom.2019.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Protective Immunity against Severe Malaria in Children Is Associated with a Limited Repertoire of Antibodies to Conserved PfEMP1 Variants

Abstract: Highlights d Group 1 and 2 DBLa domains are serodominant in PNG children exposed to malaria d Antibodies against individual DBLa are weakly associated with risk of clinical malaria d Antibodies against specific conserved DBLa are strongly associated with severe malaria d Protective DBLa antibodies are potential biomarkers for severe disease risk

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 59 publications
2
49
0
Order By: Relevance
“…Similarly, antibodies against EPCR-binding CIDRα1 domains are acquired more rapidly than antibodies against other CIDR domains in areas of high malaria transmission intensity and are boosted by severe malaria but not uncomplicated malaria (28,29). However, a recent study showed that antibodies against both rosetting-associated DBLα variants and CD36-binding CIDR domains predicted reduced risk of severe malaria to a similar extent as antibodies against EPCR-binding CIDR domains (30). The same study also showed that antibodies against group 2 DBLα variants, which are associated with rosetting (31), also predicted protection from uncomplicated malaria.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, antibodies against EPCR-binding CIDRα1 domains are acquired more rapidly than antibodies against other CIDR domains in areas of high malaria transmission intensity and are boosted by severe malaria but not uncomplicated malaria (28,29). However, a recent study showed that antibodies against both rosetting-associated DBLα variants and CD36-binding CIDR domains predicted reduced risk of severe malaria to a similar extent as antibodies against EPCR-binding CIDR domains (30). The same study also showed that antibodies against group 2 DBLα variants, which are associated with rosetting (31), also predicted protection from uncomplicated malaria.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
“…Thus, the role of rosetting in severity of malarial disease remains unclear. Nevertheless, disruption of rosettes by targeting DBL1α has been used as a vaccine strategy (53), and antibodies against rosetting-associated group 2 DBLα domains predicted protection from uncomplicated malaria, suggesting a protective role for these antibodies in less severe disease (30,31). Although speculative, it is possible that naturally acquired CIDRγ-specific IgG confers protection from febrile malaria by blocking rosette formation.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
“…Thus, the role of rosetting in severity of malarial disease remains unclear. Nevertheless, disruption of rosettes by targeting DBL1α has been used as a vaccine strategy (53), and antibodies to rosetting-associated group 2 DBLα domains predicted protection from uncomplicated malaria, suggesting a protective role for these antibodies in less severe disease (30, 31). Although speculative, it is possible that naturally acquired CIDRγ-specific IgG confers protection from febrile malaria by blocking rosette formation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, antibodies to EPCR-binding CIDRα1 domains are acquired more rapidly than antibodies to other CIDR domains in areas of high malaria transmission intensity and are boosted by severe malaria but not uncomplicated malaria (28, 29). However, a recent study showed that antibodies to both rosetting-associated DBLα variants and CD36-binding CIDR domains predicted reduced risk of severe malaria to a similar extent as antibodies to EPCR-binding CIDR domains (30). The same study also showed that antibodies to group 2 DBLα variants, which are associated with rosetting (31), also predicted protection from uncomplicated malaria.…”
Section: Introductionmentioning
confidence: 99%
“…Parasite antigens are exported to the surface of infected erythrocytes where they are accessible to antibody for hours. Among these, the variant surface antigen family PfEMP1 is immunodominant, mediates parasite sequestration and hence virulence of P. falciparum, and is a target of naturally acquired protective antibody 63 . However its highly polymorphic sequence, large size, and cysteine-rich conformational structure have impeded vaccine development and no trials of PfEMP1-based vaccines have been reported.…”
Section: Novel Bsv Antigensmentioning
confidence: 99%